EFEKTIVITAS EVALUASI FORMATIF DALAM MENINGKATKAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Siregar, Intan Suriani; Situmorang, Putri Claudia; Sihombing, Aisyah; Khairiyah, Annisa; Daulay, Yudha Darmansyah; Manjani, Nurhudayah (Universitas Negeri Medan, 2025)
This study aims to examine the effect of formative assessment on elementary school students’ learning achievement. The background of this research is the limited implementation of formative assessment in classroom learning, where assessment practices tend to focus on summative tests rather than continuous evaluation of the learning process. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The study was conducted at a public elementary school in Bandung during the 2024/2025 academic year. The participants consisted of two fifth-grade classes, with one class assigned as the experimental group implementing formative assessment strategies and the other as the control group using conventional assessment methods. Data were collected over a six-week period through learning achievement tests and classroom observations. The results of the data analysis revealed a significant difference in post-test scores between the experimental and control groups. Students who experienced formative assessment showed higher learning achievement compared to those who received conventional assessment. In addition, formative assessment was found to increase student motivation, participation, and engagement in the learning process. These findings indicate that formative assessment is effective in improving students’ learning achievement and supporting a more meaningful and student-centered learning environment in elementary schools.